2003
DOI: 10.17796/jcpd.26.2.t6601j3618675326
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial, behavioral and environmental factors associated with early childhood caries

Abstract: The goals of this cross-sectional study were to characterize and compare demographic, behavioral, and environmental factors potentially associated with early childhood caries (ECC) and to assess salivary levels of mutans streptococci (MS) and lactobacilli (LB) in underserved, predominantly Hispanic children. One hundred forty-six children aged 3 to 55 months with a range of caries experience were identified and examined. ECC was primarily associated with the presence of MS and lack of access to dental care. Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
96
3
14

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(124 citation statements)
references
References 29 publications
11
96
3
14
Order By: Relevance
“…Dental caries, one of the most common infectious diseases in humans, is still a significant public health problem in several countries (1). Mutans streptococci (MS) (Streptococcus mutans and Streptococcus sobrinus), the most common pathogens isolated from human dental plaque, are considered the major etiologic agents of caries disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dental caries, one of the most common infectious diseases in humans, is still a significant public health problem in several countries (1). Mutans streptococci (MS) (Streptococcus mutans and Streptococcus sobrinus), the most common pathogens isolated from human dental plaque, are considered the major etiologic agents of caries disease.…”
Section: Introductionmentioning
confidence: 99%
“…Mutans streptococci (MS) (Streptococcus mutans and Streptococcus sobrinus), the most common pathogens isolated from human dental plaque, are considered the major etiologic agents of caries disease. Epidemiological studies have reported that S. mutans is more prevalent than S. sobrinus in dental plaque (1,2), but have also shown that the prevalence of S. sobrinus is more closely associated with a high caries incidence (3).…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34] Relationship among ECC and the financial status has been very much reported. Children with a background marked by dental caries, whose parents and siblings have serious dental caries, are viewed as being at high risk of having dental caries in their future.…”
Section: Environmental Risk Factorsmentioning
confidence: 99%
“…Cárie de Primeira Infância (CPI) é uma doença infecciosa e transmissível na dentição decídua, com uma etiologia complexa e multifatorial, envolvendo microorganismos cariogênicos, carboidratos fermentáveis e superfícies dentárias suscetíveis 42 . A cárie dentária se constitui um grande problema de saúde pública nos países subdesenvolvidos 43 e no Brasil.…”
Section: á R I E D E N T á R I Aunclassified